Self-Powered Carbon Ink/Filter Paper Flexible Humidity Sensor Based on Moisture-Induced Voltage Generation - Li, Xiaoqiang (Langmuir : the ACS journal of surfaces and colloids, 2022)
Cellulose paper-based materials are highly flexible, hydrophilic, low-cost, and environmentally friendly and are good substrates for use as humidity sensors. Therefore, developing a paper-based humidity sensor with facile fabrication, low cost, and high sensitivity is important for expanding its practical applications. Herein, we propose a CI/FP self-powered humidity sensor based on everyday items such as writing and drawing carbon ink (CI), cellulose filter paper (FP), and polyester conductive adhesive tape, which is fabricated with the help of facile dip-coating and pasting methods. This sensor is self-powered, and the paper-based material itself can absorb water molecules in a humid environment to generate humidity-related voltage and current, which can indirectly reflect the ambient humidity level. They are characterized by a wide relative humidity (RH) sensing range (11-98%), good linearity (R2 = 0.97011), high response voltage (0.19 V), and excellent flexibility (over 1000 bends). This humidity sensor can be successfully applied to monitor human health (breathing, coughing), air humidity, and noncontact humidity sensing (skin, wet objects). This work not only proposes a low-cost and facile method for flexible humidity sensors but also provides a valuable strategy for the development of self-powered wearable electronics